Understanding behavior in the context of time : theory, research, and application - Strathman, Alan; Joireman, Jeff (Jeffrey A.) (Lawrence Erlbaum Associates, Publishers, 2005)
Time perspective influences such outcomes as attitude change, health behavior, aggression, academic work, and social dilemmas. This review of the classic and contemporary research on temporal orientation brings together social behaviors influenced by time perspective.